Implikasi pedagogis al-Qur’an surah Al-Ahzab ayat 45-48 mengenai tugas dan fungsi guru sebagai pendidik - Muhammad Tang S; Muslimah Muslimah; Akhmad Riadi; Mukmin Mukmin (Ta'dibuna, 2021)
The actualization of the values that existed in the holy book of the Al-Qur'an is expected to become a main reference in the pedagogic development. For many years, various studies on teachers in Islamic education based on the interpretation of the holy verses of the Al-Qur'an have been carried out. Therefore, this study aims to determine the pedagogical implications of QS Al-Ahzab verses 45-48 regarding teachers' duties and functions as educators. This research is a qualitative study, by using library research with content analysis took to explore the meaning of the text. Primary data took from various interpretations of the commentators regarding QS. Al-Ahzab verses 45-48, and secondary data are taken from literature such as articles from Islamic education journals and others. Data were analyzed by taking notes, selecting, analyzing, and classifying materials related to the research. From the results of the study, it is known that the pedagogical implications of QS. Al-Ahzab verses 45-48 regarding teachers' duties and functions as educators are as supervisors, entertainers, reminders, calls, and lights for students. This study's results are expected to become a theoretical reference regarding teachers' pedagogical theory in carrying out their profession.   Abstrak Aktualisasi nilai yang terkandung di dalam kitab suci Al-Qur’an diharapkan menjadi referensi sentral dalam perkembangan ilmu pedagogi sehingga berbagai kajian mengenai guru dalam konteks pendidikan Islam yang berdasarkan penafsiran ayat-ayat suci Al-Qur’an telah dilakukan. Penelitian ini bertujuan untuk mengetahui implikasi pedagogis yang terkandung di dalam QS. Al-Ahzab ayat 45-48 mengenai tugas dan fungsi guru sebagai pendidik. Penelitian ini merupakan penelitian kualitatif kajian pustaka Library Research dengan metode analisis konten content analysis untuk menggali makna teks. Data primer diambil dari berbagai penafsiran para mufasir mengenai QS. Al-Ahzab ayat 45-48, dan data sekunder diambil dari literatur berupa artikel dari jurnal ilmu pendidikan Islam dan jurnal lain yang relevan. Data dianalisis dengan menginventarisasi, memilih, menelaah, dan mengelompokkan bahan-bahan pustaka yang sesuai dengan penelitian. Dari hasil kajian diketahui bahwa implikasi pedagogis QS. Al-Ahzab ayat 45-48 tentang tugas dan fungsi guru sebagai pendidik adalah sebagai pengawas, penghibur, pengingat, penyeru dan penerang bagi anak didik. Hasil kajian ini diharapkan menjadi referensi teori mengenai ilmu pedagogi bagi guru dalam menjalankan tugas dan fungsinya sebagai pendidik.